CELLULAR LIGHT WEIGHT CONCRETE BLOCKS - Sharad Kalyan Pawar; Prafulla Suhash Kamble (International Journal of Innovations in Engineering Research and Technology, 2022)
Cellular light weight concrete (CLC) is not a new invention in concrete world. It has been gained popularity due to its lower density and comparative strength than conventional brick. CLC is versatile material which is made up of cement, fly ash and foaming agent. CLC gives better sound insulation, thermal insulation, durable, light weight, uniform size & shape, low permeability. Cellular light weight concrete is popular because of its light weight which reduces self-weight of the structure. In this project, CLC cubes are casted with 60% of fly ash and 40% of cement with foam added in time interval of 40 seconds. To check the properties of these cellular light weight cubes, the tests like density, compressive strength and water absorption test is done in laboratory. From the result, it is observed that compressive strength for CLC cubes decreases from 23.59MPa to 1.55MPa for 28days of curing and increases in water absorption from 8.36% to 13.75% due increase in the air voids. The blocks are casted by adding foam in 180sec in order to obtain compressive strength greater than 3.5MPa that can be used for load bearing walls.